Antiretroviral therapy containing raltegravir to prevent mother-to-child transmission of HIV in infected pregnant women - Diego M. Cecchini; Marina G. Martinez; Laura M. Morganti; Claudia G. Rodriguez (MDPI AG, 2017)
We conducted a retrospective study in a general hospital in Buenos Aires, Argentina (2009-2015) aimed at evaluating outcomes in HIV-infected pregnant women (HIPW), who were prescribed raltegravir (RAL)- containing antiretroviral therapy (ART). A total of 239 HIPW were enrolled in our study; among them 31 received RAL (12.9%) at different clinical stages: i) intensification (INS): addition of RAL to current ART because of detectable antepartum viral load, 13 (41.9%); ii) late presenter (LP): standard ART + RAL as fourth drug, 15 (48.4%); iii) treatment of resistant-HIV: 3 (9.7%). Median gestational age at RAL initiation was 34 weeks and median exposure was 30 days. In INS-group, median viral load (VL) decrease was 1.48 log10. In LPgroup, median VL decline was 2.15 log10. No clinical adverse events or maternal intolerance attributable to RAL were observed. Elective cesarean section was done in 51.7%; mild elevation of transaminases was observed in 35% of neonates. No vertical transmission was documented.